PENGARUH LATIHAN JUMP OVER THE BENCH TERHADAP EXPLOSIVE POWER OTOT TUNGKAI PADA TIM VOLI PUTRA SMK LABOR BINAAN FKIP UNRI - M.Rizky Mappesona A; Ramadi '; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This research want to know is there any effect of Jump Over The Bench exercise toward the explosive power of leg mucle of SMK LABOR BINAAN FKIP UNRI Pekanbaru man vollyball club, so when do smash, the player get the good jump.This research was experimental research. The population in this research was the man athletes off vollyball SMK LABOR BINAAN FKIP UNRI Pekanbaru,while the sample was all of the man athletes SMK LABOR BINAAN FKIP UNRI Pekanbaru, the total sampling is 12 person. The instrument was used Vertical Power Jump, the purpose is to measure the explosive power of leg muscle. The data was analyzed by using statistic to examine the normality with liliefors test on the significant level α 0,05. The submitted hyphothesis was there is a significant effect of Jump Over The Bench exercise toward the explosive power of leg muscle. It shows that the data was normal.Based on the data analysis, t-test showed Tcount was 6,343 and Ttable was 1,796. It means that Tcount > Ttable. Based on the statistic data analysis, the average of pree_test was 9,61 and the average of post_test was 10,16. In conclusion, there was a significant effect of Jump Over The Bench exercise toward the explosive power of leg muscle of SMK LABOR BINAAN FKIP UNRI Pekanbaru man vollyball club.Keywords : Jump Over The Bench, the Explosive Power of leg muscle